Prediction by Improving the Characteristics of Compaction and Strength in the Expansive Soils According to its Content of Sand - الزاوي منذر; عبدالله صفوان; ابراهيم جهاد; النمر عمار (Latakia University Journal -Engineering Sciences Series, 2020)
Clayey soils often showed undesirable mechanical and physical characteristics such as low bearing capacity, swelling and shrinkage characteristics. To overcome on the problems of expansive clayey soils we tend to improve their physical properties and mechanical behavior by adding various percentages of sand as a weight of soil to evaluate its effect on the following characteristics: soil texture (aterberg limits), dry density and optimum moisture (Standard Proctor test), strength and stiffness (unconfined pressure and Consolidation tests) and permeability. The obtained results refer to appreciably improvement in soil texture, strength, stiffness, permeability and volumetric changes. In addition to a significant variation in the moisture-density relationship. It is found that the optimum percentage of adding sand should not be less than 30% in the soil tested to be used in civil constructions.